Aluminum-based ceramic composite coating as well as preparation method and application thereof
By adding trace nanotitanium metal to the aluminum-based ceramic composite coating and using arc spraying technology to promote self-propagation and exothermic reaction, the problem of low bond strength of traditional coatings in marine environments is solved, and an aluminum-based ceramic composite coating with high bond strength, wear resistance and corrosion resistance is achieved, which is suitable for key components in extreme operating conditions.
Patent Information
- Application Number
- CN202411942262.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-27
AI Technical Summary
Traditional thermal spray aluminum and aluminum alloy coatings are difficult to meet the needs of long-life protection in marine environments due to low bonding strength, poor wear resistance and insufficient corrosion resistance.
By adding trace amounts of nanotitanium metal to the powder core material, and using arc spraying to quickly dynamic physicochemical metallurgy in the high-temperature arc area, it promotes a self-propagation exothermic reaction between nanotitanium and aluminum alloy, improves the wettability of the interface between aluminum and alumina ceramics, and forms an interface with high binding strength.
It realizes the high bonding strength, wear resistance and corrosion resistance of aluminum-based ceramic composite coating, extends the service life of the coating, and is suitable for key components of aerospace, water conservancy and marine and defense equipment under extreme operating conditions.
Smart Images

Figure CN119753556A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an aluminum-based ceramic composite coating and a preparation method and application thereof, and in particular to a method, coating and application for improving the bonding strength of an aluminum-based ceramic composite coating based on a dynamic metallurgical self-propagating exothermic reaction, and belongs to the field of material surface engineering and remanufacturing technology. Background Art
[0002] Marine engineering equipment is the material prerequisite for expanding marine space and developing marine resources. However, marine equipment has been in service for a long time in harsh marine environments, and it is impossible to avoid corrosion damage, abrasion failure and biological fouling, which will bring huge economic losses. Advanced high-speed arc spraying technology is one of the key technologies for realizing large-scale marine engineering corrosion protection. By preparing high-performance coatings, the surface performance of key components of marine engineering equipment can be improved and the service life can be extended. It is an important way to improve the overall level of marine engineering equipment in my country. However, the marine environment involves complex factors in many fields such as meteorology, fluid, physics, chemistry and biology. With the continuous expansion of my country's marine industry "going deep and deep", traditional thermal spraying aluminum and aluminum alloy coatings have low bonding strength (≤18MPa), poor wear resistance (hardness ≤60HV), and insufficient corrosion resistance (neutral salt spray resistance <380h). It is difficult to meet the long-life protection system of engineering components in harsh marine environments. By adding ceramic reinforcement phases, its comprehensive performance can be improved. Al2O3 ceramics are a material with high strength, high hardness and excellent corrosion resistance. They are often used in aerospace, machinery, chemical industry and other fields. Although the Al2O3 / Al composite coating has high hardness and friction coefficient, due to the presence of a large number of hard ceramic phases in the coating, the coating will produce large thermal stress during the spray heating and cooling process, making the coating toughness low. At the same time, the linear expansion coefficient between the Al2O3 ceramic and the Al metal matrix is large, the wettability is poor, and the bonding strength of the coating is not high (≤20MPa); and due to the presence of the weak metal phase in the coating, the metal phase is still the weak link in the wear of the metal ceramic coating, especially in the heavy load, corrosion, high temperature alternating wear environment, due to the insufficient bonding strength between the Al2O3 ceramic and the Al metal matrix, the strength and corrosion resistance of the Al metal phase are weak, and the wear, corrosion, tearing, and peeling of the coating are significantly aggravated, thereby restricting the service life of the composite coating. Therefore, how to improve the bonding strength of the aluminum-based ceramic coating to improve the overall mechanical properties of the coating has become a technical problem that needs to be solved in this field. Summary of the invention
[0003] In order to solve the technical problem of poor bonding strength between aluminum alloy coating and aluminum / aluminum oxide ceramic composite coating, the purpose of the present invention is to provide a method for preparing aluminum-based ceramic composite coating. To realize this idea, the shell-core structure of alumina ceramic coated with trace nano-titanium metal is used as the starting point. The purpose is to promote the self-propagating exothermic reaction between nano-titanium and aluminum alloy outer skin in the powder core wire by rapid dynamic physical and chemical metallurgy in the high-temperature arc zone of arc spraying, thereby expanding the range of solid phase and liquid phase interval, improving the wettability of the interface between aluminum and alumina ceramic and forming an interface with the alumina ceramic phase, while improving the bonding strength between ceramic particles and metal matrix, reducing splashing, allowing more alumina ceramic particles to be deposited in the coating, and improving the coating density, thereby achieving further improvement of the bonding strength, corrosion resistance and wear resistance of the composite coating. Therefore, the aluminum-based ceramic coating prepared by the method of the present invention can obtain higher cohesive bonding strength and interface bonding strength, while having both anti-slip and excellent wear and corrosion resistance.
[0004] At the same time, the present invention provides an aluminum-based ceramic composite coating, which can obtain higher cohesive bonding strength and interface bonding strength, and has both anti-skid and excellent wear and corrosion resistance.
[0005] At the same time, the present invention provides an aluminum-based ceramic composite coating for use in key components of aerospace, water conservancy, ocean, and national defense equipment.
[0006] In order to solve the above technical problems, the technical solution adopted by the present invention is:
[0007] A method for preparing an aluminum-based ceramic composite coating comprises the following steps:
[0008] Step 1: mixing alumina ceramic particles and titanium powder by acoustic resonance to obtain a metal-coated ceramic composite powder with a core-shell structure;
[0009] Step 2, wrapping the composite powder with an aluminum alloy outer skin and obtaining an aluminum-based ceramic powder core wire through a drawing process;
[0010] Step three, using high-speed arc spraying technology to spray the powder core wire material, and obtaining an aluminum-based ceramic composite coating through a dynamic metallurgical self-propagating exothermic reaction in the arc zone.
[0011] Preferably, in step 1, the particle sizes of the titanium powder and the alumina ceramic particles are 30-50 nm and 150-200 μm, respectively; and the mass ratio is (0.1-1):(99.9-99).
[0012] Preferably, in step one, the method of acoustic resonance mixing is: first set the acceleration at 50-60g to adjust the vibration frequency to 50-60Hz, then increase it from 50-60Hz to 120-140Hz at a rate of 14-30Hz / min within 3-5min, then decrease it to 0Hz at a rate of 30-50Hz / min, stop for 1-2min, then adjust it to 50-60Hz within 30s, then increase it from 50-60Hz to 120-140Hz at a rate of 14-30Hz / min within 3-5min, then decrease it to 0Hz at a rate of 30-50Hz / min, stop for 1-2min, and repeat this process until the total time is 15-30min.
[0013] Preferably, in step 2, the outer skin of the powder core is an aluminum alloy strip, the filling rate of the powder core wire is 45% to 55%; and the diameter of the powder core wire is 3±0.1 mm.
[0014] Preferably, the aluminum alloy strip is a 5054 aluminum alloy strip.
[0015] Preferably, in step three, the spraying process is: spraying voltage 35-45V, current 250-350A, spraying pressure 0.6-0.7MPa, and spraying distance 100-200mm.
[0016] The aluminum-based ceramic composite coating obtained by the preparation method of the aluminum-based ceramic composite coating of the present invention has a volume fraction of alumina ceramics ≥45 vol%.
[0017] The aluminum-based ceramic composite coating of the present invention has a coating bonding strength of ≥35MPa, an average hardness of ≥650HV0.1, a porosity of ≤1%, and a neutral salt spray resistance of ≥3000h; the coating friction coefficient is ≥1.05 in both dry and artificial seawater wet states, and the coating friction coefficient is ≥0.9 under lubricating oil conditions; and the coating neutral salt spray resistance is ≥800h after being flushed with a 1500°C oxyacetylene flame for 20s.
[0018] The aluminum-based ceramic composite coating of the present invention is used in key components of aerospace, water conservancy, ocean, and national defense equipment. The key components include ship flight decks, hulls, and drilling platforms; ship flight decks include large ship flight decks and carrier-based aircraft take-off and landing areas.
[0019] A ship flight deck is prepared by using the aluminum-based ceramic composite coating of the present invention.
[0020] Specifically, the preparation method of an aluminum-based ceramic composite coating of the present invention is as follows: first, nano-titanium metal powder and alumina ceramic particles are weighed and packaged separately at room temperature, dried in a vacuum drying oven at 100-120°C for 2-3 hours, naturally cooled and stored in a dry environment, and the packaged nano-titanium metal powder and alumina ceramic particles are placed in an acoustic resonance mixing container according to a mass percentage of (0.1-1): (99.9-99), wherein the particle size of the nano-titanium metal powder is 30-50nm, the particle size of the alumina ceramic is 150-200μm, and the capacity of the mixing container is 500ml. After the mixing container is filled with argon gas, frequency conversion-intermittent acoustic resonance mixing is performed at room temperature. After the acoustic resonance mixing is completed, the treated powder is collected, vacuumized and sealed for storage, so as to obtain a nano-titanium metal-coated alumina ceramic composite powder with a core-shell structure. Secondly, the 5054 aluminum alloy strip is tied into a U shape, and the composite powder is added into the U-shaped groove with a filling rate of 45% to 55%; the U-shaped groove is closed to allow the powder to be coated therein, and then the wire is gradually reduced to Φ3±0.1mm through a wire drawing die. Finally, the aluminum-based composite ceramic coating is prepared on the sandblasted steel substrate using high-speed arc spraying technology.
[0021] Beneficial effects: Compared with the prior art, the present invention has the following advantages:
[0022] (1) The present invention addresses the technical difficulty of low bonding strength of conventional arc sprayed aluminum / alumina ceramic composite coatings. Based on the self-propagating exothermic reaction between aluminum and titanium (generating -142.25 kJ / mol of heat), the present invention proposes a design concept of expanding the liquid phase and solid phase interval, improving the wettability between liquid metal and ceramic particles and between coating and substrate, and promoting the bonding between metal and ceramic to enhance the bonding strength by adding a trace amount of titanium metal to the powder core material and realizing the self-propagating exothermic reaction between titanium and aluminum metals in the rapid dynamic physical and chemical metallurgical process of the high-temperature arc zone of arc spraying, thereby achieving the preparation of aluminum-based ceramic coatings with high bonding strength.
[0023] (2) By designing the "shell-core structure of nano-titanium metal-coated alumina ceramics", the problem of uniform distribution of trace additives between traditional metal ceramics after mechanical and ball milling is effectively avoided, thereby improving the bonding strength of the aluminum-based ceramic composite coating and increasing its overall service life; and the entire process can be completed using low-cost high-speed arc spraying technology, which greatly improves the preparation and production efficiency and is conducive to industrial development.
[0024] (3) By improving the interface bonding state between the aluminum matrix and the alumina ceramic, the initiation and development of coating cracks can be suppressed and reduced by utilizing the load-bearing effect of the high-hardness alumina ceramic particles and the high-toughness metal aluminum matrix to absorb the impact and friction of the coating. In addition, the two have a good match in physical and chemical properties to achieve strong and tough integration of high-ceramic content coatings. This can be used for the manufacture and operation and maintenance of key components of equipment in the fields of aerospace, water conservancy, ocean, national defense science and technology, etc. that serve under extreme working conditions. It has important economic value and promotion significance.
[0025] (4) The aluminum-based ceramic composite coating obtained by the present invention can be used in strong corrosion areas at normal temperature such as ship decks, hulls and drilling platforms, and can also be used in the take-off and landing area of carrier-based aircraft on the flight deck of large ships. The anti-slip coating of the present invention can not only withstand the erosion of high-temperature tail flame flow during the take-off and landing of carrier-based aircraft, but also has strong corrosion resistance and high-temperature alternating wear and corrosion resistance, which can significantly improve the service life of the flight deck of large ships.
[0026] The present invention discloses an aluminum-based ceramic composite coating and its preparation method and application, which include the following steps: firstly, mixing alumina ceramic particles and titanium powder by acoustic resonance to obtain metal-coated ceramic composite powder with a core-shell structure; secondly, wrapping the composite powder with an aluminum alloy outer skin and obtaining an aluminum-based ceramic powder core wire by a drawing process; finally, spraying the powder core wire under preset process parameters by high-speed arc spraying technology, and realizing the preparation of high-bonding strength aluminum-based ceramic composite coating by dynamic metallurgical self-propagating exothermic reaction in the arc zone. Based on the self-propagating exothermic chemical reaction between metal aluminum and titanium, the present invention proposes a design idea of aluminum-based powder core wire with a core-shell structure of nano-titanium metal-coated alumina ceramic, and uses high-speed arc spraying high-temperature arc zone rapid dynamic physical and chemical metallurgy to promote exothermic reaction between each component, improve the wettability of metal aluminum and alumina ceramic phase and form interfacial bonding with them, while improving the bonding strength of the aluminum-based ceramic composite coating, the ceramic content and density in the coating are increased, and the wear resistance and corrosion resistance of the aluminum-based ceramic composite coating are further improved. The present invention effectively solves the technical problems of failure such as corrosion, wear and peeling that occur easily in traditional arc sprayed alumina / aluminum composite coatings under harsh service environments, and can be used for the manufacture and operation and maintenance of key components of equipment in the fields of aerospace, water conservancy, ocean, national defense science and technology, etc. that serve under extreme working conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is the appearance morphology of the core-shell composite powder prepared in Example 1;
[0028] Figure 2 is a cross-sectional morphology of the coating prepared in Example 2;
[0029] Figure 3 is the X-ray diffraction pattern of the coating prepared in Example 3;
[0030] Figure 4 is a surface morphology image of the coating prepared in Example 3 after the neutral salt spray test;
[0031] Figure 5 is the average hardness distribution of the coating prepared in Example 4;
[0032] Figure 6 is a bonding strength distribution diagram of the coating prepared in Example 5;
[0033] Figure 7 This is the potentiodynamic polarization curve of the coating prepared in Example 6. DETAILED DESCRIPTION
[0034] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments. The following embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention.
[0035] Unless otherwise specified, other materials and raw materials used in the present invention are conventional raw materials that can be purchased from the market. The technical means used are conventional means well known to those skilled in the art.
[0036] The test method used in the embodiment is as follows:
[0037] (1) The physical structure of the prepared samples was determined using an X-ray diffractometer.
[0038] (2) The morphology of the prepared powders was observed using a scanning electron microscope.
[0039] (3) The microhardness of the coating was measured using a Vickers hardness tester.
[0040] (4) The electrochemical corrosion performance of the coating was measured using an electrochemical workstation.
[0041] (5) The bonding strength of the coating was measured using a tensile bonding strength test.
[0042] (6) Use a salt spray test chamber to test the neutral salt spray resistance of the coating.
[0043] Example 1
[0044] A method for preparing an aluminum-based ceramic composite coating, the method comprising the following steps: first, weighing and packaging nano-titanium metal powder and alumina ceramic particles respectively at room temperature, drying them in a 120°C vacuum drying oven for two hours and then naturally cooling them in a dry environment, placing the packaged nano-titanium metal powder and alumina ceramic particles in an acoustic resonance mixing container at a mass percentage of 0.1:99.9, wherein the particle size of the nano-titanium metal powder is 50nm, the particle size of the alumina ceramic is 200μm, and the capacity of the mixing container is 500ml. After the mixing container is filled with argon, the acoustic resonance mixing is carried out at room temperature. The process of acoustic resonance mixing is as follows: first, the acceleration of the acoustic resonance is set to 50g, then the vibration frequency is adjusted to 50Hz, then the rate of 14Hz / min is increased from 50Hz to 120Hz within 5min, then the rate of 30Hz / min is reduced to 0Hz, stop for 1min, then adjusted to 50Hz within 30s, then the rate of 14Hz / min is increased from 50Hz to 120Hz within 5min, then the rate of 30Hz / min is reduced to 0Hz, stop for 1min, and so on and so forth until the total time is 30min. After the end, the treated powder is collected, vacuum-sealed and stored, and a nano-titanium metal-coated alumina ceramic composite powder with a shell-core structure is obtained. Secondly, the 5054 aluminum alloy strip is tied into a U shape, and the above composite powder is added into the U-shaped groove with a filling rate of 50%; the U-shaped groove is closed so that the powder is coated therein, and then the wire drawing die is passed to gradually reduce the diameter to a Φ3mm finished wire. Finally, the aluminum-based composite ceramic coating was prepared on the sandblasted steel substrate by high-speed arc spraying technology. The spraying process parameters were as follows: spraying voltage of 35 V, spraying current of 280 A, spraying distance of 200 mm, and spraying gas pressure of 0.7 MPa.
[0045] The volume fraction of alumina ceramic in the coating is 45 vol%.
[0046] Figure 1 The appearance morphology of the core-shell composite powder prepared in Example 1 shows that the composite powder has a core-shell structure and the metal coating is dense and complete. The average hardness of the aluminum-based ceramic composite coating is 661HV, the porosity is 0.9%, the average bonding strength is 35MPa, and the coating has a neutral salt spray resistance of 3000h; the friction coefficient of the coating is 1.05 in both dry and artificial seawater wet states, and the friction coefficient of the coating is 0.9 under lubricating oil conditions; after being washed with 1500℃ oxyacetylene flame for 20s, the coating has a neutral salt spray resistance of 800h.
[0047] An aluminum-based ceramic composite coating is obtained by using the preparation method of an aluminum-based ceramic composite coating of this embodiment.
[0048] The aluminum-based ceramic composite coating of this embodiment is used in key components of aerospace, water conservancy, ocean, and national defense equipment. The key components include ship flight decks, hulls, and drilling platforms; ship flight decks include the take-off and landing area of carrier-based aircraft on large ship flight decks.
[0049] A ship flight deck is prepared by using the aluminum-based ceramic composite coating of this embodiment.
[0050] Example 2
[0051] A method for preparing an aluminum-based ceramic composite coating, the method comprising the following steps: first, weighing and packaging nano-titanium metal powder and alumina ceramic particles respectively at room temperature, drying them in a 120°C vacuum drying oven for two hours and then naturally cooling them and storing them in a dry environment; placing the packaged nano-titanium metal powder and alumina ceramic particles in an acoustic resonance mixing container at a mass percentage of 0.3:99.7, wherein the particle size of the nano-titanium metal powder is 40nm, the particle size of the alumina ceramic is 180μm, and the capacity of the mixing container is 500ml. After the mixing container is filled with argon, the acoustic resonance mixing is carried out at room temperature. The process of acoustic resonance mixing is as follows: first, the acceleration of the acoustic resonance is set to 60g, then the vibration frequency is adjusted to 50Hz, then the rate of 30Hz / min is increased from 50Hz to 140Hz within 3min, then the rate of 50Hz / min is reduced to 0Hz, stop for 2min, then adjusted to 50Hz within 30s, then the rate of 30Hz / min is increased from 50Hz to 140Hz within 3min, then the rate of 50Hz / min is reduced to 0Hz, stop for 2min, and so on and so forth until the total time is 20min. After the end, the treated powder is collected, vacuum-sealed and stored, and a nano-titanium metal-coated alumina ceramic composite powder with a shell-core structure is obtained. Secondly, the 5054 aluminum alloy strip is tied into a U shape, and the above composite powder is added into the U-shaped groove with a filling rate of 45%; the U-shaped groove is closed so that the powder is coated therein, and then the wire drawing die is passed to gradually reduce the diameter to a Φ3mm finished wire. Finally, the aluminum-based composite ceramic coating was prepared on the steel substrate after sandblasting roughening by high-speed arc spraying technology. The spraying process parameters were spraying voltage of 35 V, spraying current of 250 A, spraying distance of 150 mm, and spraying gas pressure of 0.65 MPa.
[0052] The volume fraction of alumina ceramic in the coating is 48 vol%.
[0053] Figure 2The cross-sectional morphology of the coating prepared for Example 2 shows that the composite coating has a compact structure, dense organization, and good bonding with the substrate. The average porosity of the tested coating is 0.75%, the coating bonding strength is 38.2MPa, and the average hardness of the coating is 673HV. The coating has a neutral salt spray resistance of 3500h; the coating friction coefficients in dry and artificial seawater wet states are 1.09 and 1.06 respectively, and the coating friction coefficient under lubricating oil conditions is 0.92; after being flushed with 1500℃ oxyacetylene flame for 20s, the coating has a neutral salt spray resistance of 880h.
[0054] An aluminum-based ceramic composite coating is obtained by using the preparation method of an aluminum-based ceramic composite coating of this embodiment.
[0055] The aluminum-based ceramic composite coating of this embodiment is used in key components of aerospace, water conservancy, ocean, and national defense equipment. The key components include ship flight decks, hulls, and drilling platforms; ship flight decks include the take-off and landing area of carrier-based aircraft on large ship flight decks.
[0056] A ship flight deck is prepared by using the aluminum-based ceramic composite coating of this embodiment.
[0057] Example 3
[0058] A method for preparing an aluminum-based ceramic composite coating, the method comprising the following steps: first, weighing and packaging nano-titanium metal powder and alumina ceramic particles respectively at room temperature, drying them in a 100°C vacuum drying oven for 3 hours and then naturally cooling them and storing them in a dry environment; placing the packaged nano-titanium metal powder and alumina powder in an acoustic resonance mixing container at a mass percentage of 1:99, wherein the particle size of the nano-titanium metal powder is 30nm, the particle size of the alumina ceramic is 200μm, and the capacity of the mixing container is 500ml. After the mixing container is filled with argon, acoustic resonance mixing is performed at room temperature. The process of acoustic resonance mixing is as follows: first, the acceleration of the acoustic resonance is set to 50g, then the vibration frequency is adjusted to 60Hz, then the rate of 26.7Hz / min is increased from 60Hz to 140Hz within 3min, then the rate of 40Hz / min is reduced to 0Hz, and the temperature is stopped for 1.5min, and then the temperature is adjusted to 60Hz within 30s, then the rate of 26.7Hz / min is increased from 60Hz to 140Hz within 3min, then the rate of 40Hz / min is reduced to 0Hz, and the temperature is stopped for 1.5min, and this is repeated until the total time is 25min. After the end, the treated powder is collected, vacuum-sealed and stored to obtain a nano-titanium metal-coated alumina ceramic composite powder with a core-shell structure. Secondly, the 5054 aluminum alloy strip was tied into a U shape, and the composite powder was added into the U-shaped groove with a filling rate of 55%; the U-shaped groove was closed to cover the powder, and then the wire was gradually reduced to Φ3mm finished wire through a wire drawing die. Finally, the aluminum-based composite ceramic coating was prepared on the sandblasted steel substrate by high-speed arc spraying technology, and the spraying process parameters were spraying voltage of 45V, spraying current of 300A, spraying distance of 180mm, and spraying pressure of 0.7MPa.
[0059] The volume fraction of alumina ceramic in the coating is 47 vol%.
[0060] Figure 3 The X-ray diffraction pattern of the coating prepared for Example 3 shows that the pure aluminum coating structure is mainly composed of αAl, while the aluminum-based ceramic coating structure is mainly composed of αAl and αAl2O3. After testing, the average porosity of the aluminum-based ceramic composite coating is 0.5%, the coating bonding strength is 41.3MPa, and the average hardness of the coating is 726HV; the coating has a neutral salt spray resistance of 3000h; the coating friction coefficients in dry state and artificial seawater wet state are 1.08 and 1.06 respectively, and the coating friction coefficient under lubricating oil conditions is 0.95; after being washed with 1500℃ oxyacetylene flame for 20s, the coating has a neutral salt spray resistance of 950h.
[0061] Figure 4This is a coating surface morphology of the coating prepared in Example 3 after the neutral salt spray test. The arc sprayed zinc-aluminum coating is used as a comparison coating. It can be seen that a large amount of white rust exists on the surface of the zinc-aluminum coating after 144 hours of the neutral salt spray test, indicating that the coating has undergone serious corrosion at this time; however, the aluminum-based ceramic composite coating prepared in this example has no white rust, bulging or other failure phenomena on the coating surface after 3000 hours of neutral salt spray, indicating that the aluminum-based ceramic coating prepared in this example has excellent corrosion resistance.
[0062] An aluminum-based ceramic composite coating is obtained by using the preparation method of an aluminum-based ceramic composite coating of this embodiment.
[0063] The aluminum-based ceramic composite coating of this embodiment is used in key components of aerospace, water conservancy, ocean, and national defense equipment. The key components include ship flight decks, hulls, and drilling platforms; ship flight decks include the take-off and landing area of carrier-based aircraft on large ship flight decks.
[0064] A ship flight deck is prepared by using the aluminum-based ceramic composite coating of this embodiment.
[0065] Example 4
[0066] A preparation method of an aluminum-based ceramic composite coating, the method comprising the following steps: first, weighing and packaging nano-titanium metal powder and alumina ceramic particles respectively at room temperature, drying them in a 120°C vacuum drying oven for two hours and then naturally cooling them in a dry environment, placing the packaged nano-titanium metal powder and alumina ceramic particles in an acoustic resonance mixing container at a mass percentage of 0.8:99.2, wherein the particle size of the nano-titanium metal powder is 50nm, the particle size of the alumina ceramic is 200μm, and the capacity of the mixing container is 500ml. After the mixing container is filled with argon, acoustic resonance mixing is performed at room temperature. The process of acoustic resonance mixing is as follows: first, the acceleration of the acoustic resonance is set to 50g, then the vibration frequency is adjusted to 55Hz, then the rate of 18.75Hz / min is increased from 55Hz to 130Hz within 4min, then the rate of 45Hz / min is reduced to 0Hz, stop for 1min, then adjusted to 55Hz within 30s, then the rate of 18.75Hz / min is increased from 55Hz to 130Hz within 4min, then the rate of 45Hz / min is reduced to 0Hz, stop for 1min, and so on and so forth until the total time is 30min. After the end, the treated powder is collected, vacuum-sealed and stored, and a nano-titanium metal-coated alumina ceramic composite powder with a core-shell structure is obtained. Secondly, the 5054 aluminum alloy strip was tied into a U shape, and the composite powder was added into the U-shaped groove with a filling rate of 48%; the U-shaped groove was closed to cover the powder, and then the wire was gradually reduced to Φ3mm finished wire through a wire drawing die. Finally, the aluminum-based composite ceramic coating was prepared on the sandblasted steel substrate using high-speed arc spraying technology, and the spraying process parameters were spraying voltage of 42V, spraying current of 350A, spraying distance of 120mm, and spraying air pressure of 0.6MPa.
[0067] The volume fraction of alumina ceramic in the coating is 49 vol%.
[0068] Figure 5 The average hardness distribution of the coating prepared in Example 4 shows that the average hardness of the aluminum-based ceramic coating is 721HV, which is much higher than that of the pure aluminum coating. After testing, the average porosity of the aluminum-based ceramic composite coating is 0.68%, and the coating bonding strength is 36.5MPa. The coating has a neutral salt spray resistance of 3500h; the friction coefficients of the coating in dry state and artificial seawater wet state are 1.1 and 1.08 respectively, and the friction coefficient of the coating under lubricating oil conditions is 0.97; after being flushed with 1500℃ oxyacetylene flame for 20s, the coating has a neutral salt spray resistance of 850h.
[0069] An aluminum-based ceramic composite coating is obtained by using the preparation method of an aluminum-based ceramic composite coating of this embodiment.
[0070] The aluminum-based ceramic composite coating of this embodiment is used in key components of aerospace, water conservancy, ocean, and national defense equipment. The key components include ship flight decks, hulls, and drilling platforms; ship flight decks include the take-off and landing area of carrier-based aircraft on large ship flight decks.
[0071] A ship flight deck is prepared by using the aluminum-based ceramic composite coating of this embodiment.
[0072] Example 5
[0073] A method for preparing an aluminum-based ceramic composite coating, the method comprising the following steps: first, weighing and packaging nano-titanium metal powder and alumina ceramic particles respectively at room temperature, drying them in a 120°C vacuum drying oven for two hours and then naturally cooling them and storing them in a dry environment; placing the packaged nano-titanium metal powder and alumina ceramic particles in an acoustic resonance mixing container at a mass percentage of 0.5:99.5, wherein the particle size of the nano-titanium metal powder is 50nm, the particle size of the alumina ceramic is 150μm, and the capacity of the mixing container is 500ml. After the mixing container is filled with argon, the acoustic resonance mixing is carried out at room temperature. The process of acoustic resonance mixing is as follows: first, the acceleration of the acoustic resonance is set to 50g, then the vibration frequency is adjusted to 60Hz, then the rate of 20Hz / min is increased from 60Hz to 120Hz within 3min, then the rate of 50Hz / min is reduced to 0Hz, stop for 1min, then adjusted to 60Hz within 30s, then the rate of 20Hz / min is increased from 60Hz to 120Hz within 3min, then the rate of 50Hz / min is reduced to 0Hz, stop for 1min, and so on and so forth until the total time is 15min. After the end, the treated powder is collected, vacuum-sealed and stored, and a nano-titanium metal-coated alumina ceramic composite powder with a shell-core structure is obtained. Secondly, the 5054 aluminum alloy strip is tied into a U shape, and the above composite powder is added into the U-shaped groove with a filling rate of 52%; the U-shaped groove is closed so that the powder is coated therein, and then the wire drawing die is passed to gradually reduce the diameter to a Φ3mm finished wire. Finally, the aluminum-based composite ceramic coating was prepared on the sandblasted steel substrate by high-speed arc spraying technology. The spraying process parameters were as follows: spraying voltage of 44 V, spraying current of 290 A, spraying distance of 100 mm, and spraying gas pressure of 0.7 MPa.
[0074] The volume fraction of alumina ceramic in the coating is 48 vol%.
[0075] Figure 6The bonding strength distribution diagram of the coating prepared in Example 5 shows that the average bonding strength of the aluminum-based ceramic coating is 39.2MPa, which is 3.1 times that of the pure aluminum coating. After testing, the average porosity of the aluminum-based ceramic composite coating is 0.82%, the average hardness of the coating is 752HV, and the neutral salt spray resistance of the coating is more than 3000h. The friction coefficients of the aluminum-based ceramic composite coating in dry state and artificial seawater wet state are 1.12 and 1.09 respectively, and the friction coefficient of the coating under lubricating oil conditions is 0.98; after being flushed with 1500℃ oxyacetylene flame for 20s, the neutral salt spray resistance of the coating is 910h.
[0076] An aluminum-based ceramic composite coating is obtained by using the preparation method of an aluminum-based ceramic composite coating of this embodiment.
[0077] The aluminum-based ceramic composite coating of this embodiment is used in key components of aerospace, water conservancy, ocean, and national defense equipment. The key components include ship flight decks, hulls, and drilling platforms; ship flight decks include the take-off and landing area of carrier-based aircraft on large ship flight decks.
[0078] A ship flight deck is prepared by using the aluminum-based ceramic composite coating of this embodiment.
[0079] Example 6
[0080] A method for preparing an aluminum-based ceramic composite coating, the method comprising the following steps: first, weighing and packaging nano-titanium metal powder and alumina ceramic particles respectively at room temperature, drying them in a 120°C vacuum drying oven for two hours and then naturally cooling them and storing them in a dry environment; placing the packaged nano-titanium metal powder and alumina powder in an acoustic resonance mixing container at a mass percentage of 0.4:99.6, wherein the particle size of the nano-titanium metal powder is 50nm, the particle size of the alumina ceramic is 200μm, and the capacity of the mixing container is 500ml. After the mixing container is filled with argon, the acoustic resonance mixing is carried out at room temperature. The process of acoustic resonance mixing is as follows: first, the acceleration of the acoustic resonance is set to 50g, then the vibration frequency is adjusted to 60Hz, then the rate of 16Hz / min is increased from 60Hz to 140Hz within 5min, then the rate of 30Hz / min is reduced to 0Hz, stop for 1min, then adjusted to 60Hz within 30s, then the rate of 16Hz / min is increased from 60Hz to 140Hz within 5min, then the rate of 30Hz / min is reduced to 0Hz, stop for 1min, and so on and so forth until the total time is 25min. After the end, the treated powder is collected, vacuum-sealed and stored, and a nano-titanium metal-coated alumina ceramic composite powder with a shell-core structure is obtained. Secondly, the 5054 aluminum alloy strip is tied into a U shape, and the above composite powder is added into the U-shaped groove, and the filling rate is 53%; the U-shaped groove is closed so that the powder is coated therein, and then the wire drawing die is passed to gradually reduce the diameter to a Φ3mm finished wire. Finally, the aluminum-based composite ceramic coating was prepared on the sandblasted steel substrate by high-speed arc spraying technology. The spraying process parameters were as follows: spraying voltage of 40 V, spraying current of 270 A, spraying distance of 180 mm, and spraying gas pressure of 0.65 MPa.
[0081] Figure 7 The potentiodynamic polarization curve of the coating prepared in Example 6 after being immersed in a 3.5wt% NaCl solution for 10 days shows that the self-corrosion current density of the aluminum-based ceramic coating is 1.132×10 -6 μA / cm 2 , the self-corrosion current density of pure aluminum coating is 34.92×10 -6 μA / cm 2 The self-corrosion current density of the aluminum-based ceramic coating is one order of magnitude higher than that of the pure aluminum coating, showing higher corrosion resistance; the self-corrosion potentials of the pure aluminum coating and the aluminum-based ceramic coating are -1.283V and -1.069V respectively. According to the test, the volume fraction of alumina ceramic in the coating is 50vol%.
[0082] The average porosity of the aluminum-based ceramic composite coating is 0.76%, the average hardness of the coating is 734HV, and the neutral salt spray resistance of the aluminum-based ceramic coating is more than 3000h. The average bonding strength of the aluminum-based ceramic coating is 42.8MPa. The friction coefficients of the aluminum-based ceramic composite coating in dry state and artificial seawater wet state are 1.11 and 1.09 respectively, and the friction coefficient of the coating under lubricating oil conditions is 0.98; after being flushed with 1500℃ oxyacetylene flame for 20s, the neutral salt spray resistance of the coating is 900h.
[0083] An aluminum-based ceramic composite coating is obtained by using the preparation method of an aluminum-based ceramic composite coating of this embodiment.
[0084] The aluminum-based ceramic composite coating of this embodiment is used in key components of aerospace, water conservancy, ocean, and national defense equipment. The key components include ship flight decks, hulls, and drilling platforms; ship flight decks include the take-off and landing area of carrier-based aircraft on large ship flight decks.
[0085] A ship flight deck is prepared by using the aluminum-based ceramic composite coating of this embodiment.
[0086] Comparative Example 1
[0087] The difference between this comparative example and Example 1 is only that:
[0088] The resonant frequency of the acoustic resonance mixing is 120 Hz; the acceleration is 50 g and the mixing time is 30 min.
[0089] The volume fraction of alumina ceramic in the coating obtained in this comparative example is 30 vol%. The coating has a bonding strength of 22 MPa, an average hardness of 350 HV0.1, a porosity of 1.79%, and a neutral salt spray resistance of 1000 h. The friction coefficients of the coating in dry state and artificial seawater wet state are 0.96 and 0.9 respectively, and the friction coefficient of the coating under lubricating oil condition is 0.80. After being washed with 1500°C oxyacetylene flame for 20 seconds, the neutral salt spray resistance of the coating is 240 h.
[0090] Comparative Example 2
[0091] The difference between this comparative example and Example 1 is that the process of acoustic resonance mixing is: first set the acceleration to 50g, then adjust the vibration frequency to 40Hz, then increase from 40Hz to 150Hz at a rate of 36.7Hz / min within 3min, then decrease to 0Hz at a rate of 20Hz / min, stop for 0.5min, then adjust to 40Hz within 30s, then increase from 40Hz to 150Hz at a rate of 36.7Hz / min within 3min, then decrease to 0Hz at a rate of 20Hz / min, stop for 0.5min, and repeat this process until the total time is 30min.
[0092] The volume fraction of alumina ceramic in the coating obtained in this comparative example is 36 vol%. The coating has a bonding strength of 25 MPa, an average hardness of 590 HV0.1, a porosity of 1.55%, and a neutral salt spray resistance of 2000 h. The friction coefficients of the coating in dry state and artificial seawater wet state are 0.97 and 0.95 respectively, and the friction coefficient of the coating under lubricating oil condition is 0.82. After being washed with 1500°C oxyacetylene flame for 20 seconds, the neutral salt spray resistance of the coating is 600 h.
[0093] Comparative Example 3
[0094] The difference between this comparative example and Example 1 is that the process of acoustic resonance mixing is: first set the acceleration to 50g, then adjust the vibration frequency to 50Hz, then increase from 50Hz to 120Hz at a rate of 14Hz / min within 5min, then decrease to 0Hz at a rate of 30Hz / min, then adjust to 50Hz within 30s, then increase from 50Hz to 120Hz at a rate of 14Hz / min within 5min, then decrease to 0Hz at a rate of 30Hz / min, and repeat this process until the total time is 30min.
[0095] The volume fraction of alumina ceramic in the coating obtained in this comparative example is 39 vol%. The coating has a bonding strength of 28 MPa, an average hardness of 600 HV0.1, a porosity of 1.38%, and a neutral salt spray resistance of 2500 h. The friction coefficients of the coating in dry state and artificial seawater wet state are 0.98 and 0.96 respectively, and the friction coefficient of the coating under lubricating oil condition is 0.84. After being washed with 1500°C oxyacetylene flame for 20 seconds, the neutral salt spray resistance of the coating is 620 h.
[0096] It should be understood that in order to streamline the present disclosure and aid in understanding one or more of the various inventive aspects, in the above description of exemplary embodiments of the present invention, various features of the present invention are sometimes grouped together into a single embodiment, figure, or description thereof. However, this disclosed method should not be interpreted as reflecting the intention that the claimed invention requires more features than those expressly recited in each claim. Rather, as reflected in the claims, inventive aspects lie in less than all of the features of the previously disclosed embodiments. Therefore, the claims that follow the detailed description are hereby expressly incorporated into the detailed description, with each claim itself serving as a separate embodiment of the present invention.
[0097] Although the present invention has been described according to a limited number of embodiments, it will be apparent to those skilled in the art, with the benefit of the above description, that other embodiments may be envisioned within the scope of the invention thus described. In addition, it should be noted that the language used in this specification is selected primarily for readability and teaching purposes, rather than for explaining or defining the subject matter of the present invention. Therefore, many modifications and variations will be apparent to those skilled in the art without departing from the scope and spirit of the appended claims. The disclosure of the present invention is illustrative, not restrictive, with respect to the scope of the present invention, which is defined by the appended claims.
[0098] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing an aluminum-based ceramic composite coating, characterized in that: The following steps are involved: Step 1: mixing alumina ceramic particles and titanium powder by acoustic resonance to obtain a core-shell structured metal-coated ceramic composite powder; Step 2, wrapping the composite powder with an aluminum alloy outer skin and obtaining an aluminum-based ceramic powder core wire through a drawing process; Step three, using high-speed arc spraying technology to spray the powder core wire material, and obtaining an aluminum-based ceramic composite coating through a dynamic metallurgical self-propagating exothermic reaction in the arc zone.
2. The method for preparing an aluminum-based ceramic composite coating according to claim 1, characterized in that: In step 1, the particle sizes of titanium powder and alumina ceramic particles are 30-50 nm and 150-200 μm respectively; the mass ratio is (0.1-1): (99.9-99).
3. The method for preparing an aluminum-based ceramic composite coating according to claim 1, characterized in that: In step one, the method of acoustic resonance mixing is: first set the acceleration at 50-60g to adjust the vibration frequency to 50-60Hz, then increase it from 50-60Hz to 120-140Hz at a rate of 14-30Hz / min within 3-5min, then decrease it to 0Hz at a rate of 30-50Hz / min, stop for 1-2min, then adjust it to 50-60Hz within 30s, then increase it from 50-60Hz to 120-140Hz at a rate of 14-30Hz / min within 3-5min, then decrease it to 0Hz at a rate of 30-50Hz / min, stop for 1-2min, and repeat this process until the total time is 15-30min.
4. The method for preparing an aluminum-based ceramic composite coating according to claim 1, characterized in that: In step 2, the outer skin of the powder core is an aluminum alloy strip, the filling rate of the powder core wire is 45% to 55%; and the diameter of the powder core wire is 3±0.1 mm.
5. The method for preparing an aluminum-based ceramic composite coating according to claim 4, characterized in that: The aluminum alloy strip is a 5054 aluminum alloy strip.
6. The method for preparing an aluminum-based ceramic composite coating according to claim 1, characterized in that: In step three, the spraying process is: spraying voltage 35-45V, current 250-350A, spraying pressure 0.6-0.7MPa, and spraying distance 100-200mm.
7. The aluminum-based ceramic composite coating obtained by the method for preparing an aluminum-based ceramic composite coating according to any one of claims 1 to 6, characterized in that: The volume fraction of alumina ceramic in the coating is ≥45 vol%.
8. The aluminum-based ceramic composite coating according to claim 7, characterized in that: The coating bonding strength is ≥35MPa, the average hardness is ≥650HV0.1, the porosity is ≤1%, and the neutral salt spray resistance is ≥3000h; the coating friction coefficient is ≥1.05 in both dry and artificial seawater wet states, and the coating friction coefficient is ≥0.9 under lubricating oil conditions; After being blasted with 1500℃ oxyacetylene flame for 20s, the neutral salt spray resistance of the coating shall be ≥800h.
9. The application of the aluminum-based ceramic composite coating according to claim 7 in key parts of aerospace, water conservancy, ocean, and national defense equipment, characterized in that: Key components include ship flight decks, hulls and drilling platforms; ship flight decks include large ship flight decks and carrier-based aircraft take-off and landing areas.
10. A ship flight deck, characterized in that: The aluminum-based ceramic composite coating is prepared using the aluminum-based ceramic composite coating described in claim 7.
Citation Information
Patent Citations
Composite powder as well as preparation method and application of composite powder
CN108237220A
Cooking utensil and preparation method thereof
CN114381681A
Broad-spectrum micro-nano ceramic reinforced titanium alloy powder based on acoustic resonance and preparation method thereof
CN117324622A
Seamless cored wire for multi-scale synergistically reinforced Al-based composite coating and preparation method of seamless cored wire for multi-scale synergistically reinforced Al-based composite coating
CN117867436A
Method for preparing nano-powder coated metal powder by adopting medium-assisted acoustic resonance mixing technology
CN118371719A
Cited By
Sulfur-corrosion-resistant cladding material for boiler tube bank and preparation method of sulfur-corrosion-resistant cladding material
CN121373433A